Effective anti-programmed death-1 therapy in a SUFU-mutated patient with Gorlin-Goltz syndrome - Moreira, Alvaro; Kirchberger, M. C.; Toussaint, Frédéric; Erdmann, M.; Schuler, Gerold; Heinzerling, Lucie (British Journal of Dermatology, 2018)
We present the case of a 77-year-old male patient with more than 50 basal cell carcinomas on the head and upper trunk. The patient did not respond to several lines of treatment, including surgery, imiquimod, retinoids, itraconazole and therapy with the hedgehog inhibitor vismodegib. The patient responded well to off-label therapy with the anti-programmed death-1 antibody pembrolizumab after four infusions.
EVALuna2:34414